Sintered pellets for reduction and method for producing same

By increasing the high viscosity slag composition in the sintered pellets and increasing the LOI value and porosity, the problem of pulverizing and cluster formation in the solid reduction furnace is solved, and stable operation and efficient production in the furnace are achieved.

CN119677882APending Publication Date: 2025-03-21JFE STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280097420.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-01
Publication Date
2025-03-21

Smart Images

  • Figure CN119677882A_ABST
    Figure CN119677882A_ABST
Patent Text Reader

Abstract

Provided are fired pellets which are effective for preventing clustering by preventing fusion by reducing the opportunity of contact between low-melting-point slags in the production of fired pellets used in a solid reduction furnace, and a method for producing the same. The present invention relates to a sintered pellet for reduction and a method for manufacturing the same. The ratio of the high-viscosity slag component (Al2O3 + MgO + SiO2) relative to the total Fe (T.Fe) in the sintered pellet for reduction satisfies the formula: (Al2O3 + MgO + SiO2) / T.Fe > = 0.09. Wherein Al2O3 is the component concentration (mass%) of Al2O3 in the fired pellets, MgO is the component concentration (mass%) of MgO in the fired pellets, SiO2 is the component concentration (mass%) of SiO2 in the fired pellets, and T.Fe is the component concentration (mass%) of T.Fe in the fired pellets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to reduced fired pellets effective for a solid reduction furnace and a method for manufacturing the same. Background Art

[0002] In recent years, in order to avoid global warming caused by the increase in CO2, various technological developments for reducing its emissions have been underway.

[0003] Under such circumstances, in the field of the iron and steel industry, an iron-making method based on a solid reduction furnace as a hydrogen-based reduction process has also attracted attention, and research on fired pellets used in this method is underway. However, in the aforementioned solid reduction furnace, when the charged raw material (fired pellets) passes through the high-temperature region in the furnace and the hematite phase in the fired pellets is reduced and changes to the magnetite phase, accompanied by volume expansion, a pulverization phenomenon occurs. In addition, it is known that in addition to the contact and fusion of metallic irons with each other, the contact and fusion of low-melting-point slags also occur. As a result, it is known that clusters occur in the furnace and the pellets in the furnace cannot move, resulting in a bridging phenomenon where the pellets cannot be taken out from the bottom of the furnace. Especially in a solid reduction furnace for hydrogen-based reduction, this clustering is a very large problem to be solved.

[0004] Under such circumstances, several prior arts have been proposed for the purpose of preventing the clusters observed in the aforementioned solid reduction furnace. For example, in Patent Document 1, a method of coating the pellet surface with Ca(OH)2 and Mg(OH)2 is proposed. In Patent Document 2, a method of preventing reduction pulverization and obtaining fired pellets with little expansion by coating the surface of fired lump ore (pellets) with powdery solid fuel is proposed. In addition, in Patent Document 3, by coating the surface of fired pellets with iron ore containing cement, clustering in the solid reduction furnace is prevented, and heat loss is reduced and operation efficiency is improved. In addition, in Patent Document 4, a technique of coating a substance containing a calcium-iron compound formed of CaxFeyOz (1 < y / x ≤ 2; 1 ≤ z) is proposed.

[0005] Prior Art Documents

[0006] Patent Documents

[0007] Patent Document 1: Japanese Patent Laid-Open No. 59-10411

[0008] Patent Document 2: Japanese Patent Laid-Open No. 62-37325

[0009] Patent Document 3: Japanese Patent Laid-Open No. 63-262426

[0010] Patent Document 4: Japanese Patent Laid-Open No. 2017-119910 Summary of the Invention

[0011] Problems to be solved by the invention

[0012] The above-mentioned prior arts (Patent Documents 1-4) are all methods of reducing the contact between the reduced metallic irons, which is the cause of the clusters observed near the high temperature area (500-600°C) in a solid reduction furnace such as a shaft furnace, mainly by the presence of non-metallic components. However, according to the inventor's research, the cluster prevention methods of the above-mentioned prior arts are insufficient. In addition, for example, a coating process of non-metallic components needs to be separately adopted, which not only increases the cost, but also requires additional special equipment.

[0013] Therefore, an object of the present invention is to provide a fired pellet and a method for producing the same, which is effective in preventing clustering by reducing the chance of contact between low-melting-point slags and preventing fusion in the production of fired pellets used in a solid reduction furnace.

[0014] Means for solving problems

[0015] The present invention is a technology developed to solve the above-mentioned problems existing in the prior art and to achieve the above-mentioned objectives. First, a sintered pellet for reduction is proposed, which is characterized in that the ratio of the high-viscosity slag component (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (1).

[0016] remember

[0017] (Al2O3+MgO+SiO2) / T.Fe≥0.09· · · (1)

[0018] Wherein, Al2O3: Al2O3 component concentration in the fired pellets (mass %)

[0019] MgO: MgO content in the fired pellets (mass %)

[0020] SiO2: Concentration of SiO2 in the fired pellets (mass %)

[0021] T.Fe: T.Fe component concentration in the fired pellets (mass %)

[0022] In addition, secondly, the present invention provides a method for producing calcined pellets for reduction, characterized in that in the production of the calcined pellets for reduction, a raw material blended so as to have an average LOI (loss on ignition) of 5% or more is used as an iron-containing raw material for reduction and calcination.

[0023] It should be noted that, for the above-mentioned calcined pellets for reduction, it is considered that the following scheme in the present invention can provide a more preferred embodiment. That is,

[0024] (a) The ratio of the high viscosity slag components (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (2),

[0025] remember

[0026] (Al2O3+MgO+SiO2) / T.Fe≥0.12· · · (2)

[0027] Wherein, Al2O3: Al2O3 component concentration in the fired pellets (mass %)

[0028] MgO: MgO content in the fired pellets (mass %)

[0029] SiO2: Concentration of SiO2 in the fired pellets (mass %)

[0030] T.Fe: T.Fe component concentration in the fired pellets (mass %)

[0031] (b) The porosity is 20% or more,

[0032] (c) The porosity is 30% or more,

[0033] In addition, in the production of calcined pellets for reduction,

[0034] (d) the iron-containing raw material is a raw material that has been pre-treated to remove water of crystallization so that the average LOI (loss on ignition) is 2% or less.

[0035] (e) the pretreatment for removing water of crystallization is performed by heating and drying in a rotary kiln, and the average LOI (loss on ignition) of the iron-containing raw material is measured by sampling at the kiln outlet.

[0036] (f) a raw material containing M.Fe is mixed to prepare a mixed raw material containing 4 mass % or more and 24 mass % or less of M.Fe, and the mixed raw material is granulated and calcined,

[0037] (g) the raw material is reduced iron having a particle size of 3 mm or less reduced in a solid reduction furnace,

[0038] (h) The reduced iron contains 78 mass % or more of M.Fe.

[0039] M.Fe represents metallic iron, and the same shall apply hereinafter.

[0040] Effects of the Invention

[0041] According to the calcined pellets for reduction of the present invention involved in the above-mentioned constitution, a relatively large amount of high-viscosity slag components (Al2O3, MgO, SiO2) are contained relative to the total iron. Thus, the generation of low-melting-point slag caused by FeO in the solid reduction furnace and its fluidity can be reduced. As a result, the chance of contact and fusion between pellets caused by the presence of such slag can be prevented, and the above-mentioned clustering in the reduction furnace, which is a problem, can be effectively prevented.

[0042] In addition, according to the manufacturing method of the present invention, by using a high LOI raw material as an iron-containing raw material, the obtained fired pellets can be made porous, thereby reducing the chance of contact between metallic irons, thereby effectively preventing clustering and improving the operating efficiency of the solid reduction furnace. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] [ Figure 1 ] is a graph showing the relationship between (Al2O3+MgO+SiO2) / T.Fe and LOI for Australian iron ore used as an iron-containing raw material. DETAILED DESCRIPTION

[0044] The solid reduction furnace used in the present invention is a furnace for using hydrogen or the like as a reducing gas, charging calcined pellets for reduction into the furnace, and reducing them to a reduction rate of 90% or more of Fe. In the operation of the solid reduction furnace, the properties of the raw materials charged into the furnace, i.e., the calcined pellets, are important.

[0045] The most important thing for the fired pellets is whether it is possible to prevent the clustering caused by the contact and fusion of the pellets in the high temperature area (500-800°C) in the aforementioned solid reduction furnace. In response to such a requirement, the present invention studies the relationship between iron-containing raw materials such as metallic iron, i.e., iron oxides such as iron ore, iron sulfide, and ironmaking dust, and high-viscosity slag components. The results show that from the perspective of the fluidity of the raw materials in the furnace, it is ideal to properly manage the relationship with the high-viscosity slag components. That is, by always producing high-viscosity slag in the furnace, undesirable flow in the high-temperature area is suppressed. In this way, the fusion of slags can be prevented, and clustering can be prevented.

[0046] As described above, it is found that in the present invention, it is effective to include a high-viscosity slag component at a certain ratio in the iron-containing raw material, iron ore, or auxiliary raw materials to be blended.

[0047] As components that can form the high-viscosity slag, particular attention is paid to (Al2O3, MgO, SiO2). When their total amount is maintained at a specified ratio relative to the total iron (T·Fe), the slags generated in the above-mentioned furnace can be effectively prevented from merging with each other.

[0048] This can be achieved by making the composition of the reduced calcined pellets contain the aforementioned highly viscous slag component (Al2O3+MgO+SiO2) at a certain ratio relative to the total iron (T·Fe) in the iron-containing raw material. That is, the calcined pellets satisfy the relationship of the following formula (1).

[0049] remember

[0050] (Al2O3+MgO+SiO2) / T.Fe≥0.09· · · (1)

[0051] In the above formula (1), Al2O3 is the component concentration (mass %) of Al2O3 in the aforementioned calcined pellet for reduction. MgO is the component concentration (mass %) of MgO in the aforementioned calcined pellet for reduction. SiO2 is the component concentration (mass %) of MgO in the aforementioned calcined pellet for reduction. T.Fe is the total Fe concentration (mass %) of the aforementioned calcined pellet for reduction.

[0052] In the present invention, from the viewpoint of preventing contact and fusion of slags in the high temperature region of the furnace, the aforementioned high viscosity slag component (Al2O3+MgO+SiO2) and total iron (T.Fe) have a more preferable relationship. That is, as shown in the following formula (2) containing a larger amount of high viscosity slag components.

[0053] remember

[0054] (Al2O3+MgO+SiO2) / T.Fe≥0.12· · · (2)

[0055] In the above formula (2), Al2O3 is the component concentration (mass %) of Al2O3 in the aforementioned calcined pellet for reduction. MgO is the component concentration (mass %) of MgO in the aforementioned calcined pellet for reduction. SiO2 is the component concentration (mass %) of MgO in the aforementioned calcined pellet for reduction. T.Fe is the total Fe concentration (mass %) of the aforementioned calcined pellet for reduction.

[0056] It should be noted that, in the present invention, the total Fe in the iron-containing raw material refers to the total value of the iron concentration derived from iron compounds (iron oxide, iron sulfide, calcium ferrite, etc.) in addition to metallic iron (M.Fe). On the other hand, the high-viscosity slag component refers to the total value of the Al2O3 concentration, MgO concentration, and SiO2 concentration contained in the auxiliary raw materials (limestone, quicklime, dolomite, etc.) and the binder (bentonite, etc.) in addition to the iron-containing raw materials such as iron ore and ironmaking dust.

[0057] The aforementioned Al2O3 concentration, MgO concentration, and SiO2 concentration can be calculated as follows. First, the Al concentration, Mg concentration, and Si concentration are measured by elemental analysis such as fluorescent X-rays. Then, the concentration of each element can be calculated by multiplying (molecular weight / atomic weight of the oxide corresponding to each unit of the element). Specifically, for example, the Al2O3 concentration can be calculated by multiplying the Al concentration measured by elemental analysis such as fluorescent X-rays by (Al2O3 molecular weight / 2) / Al atomic weight=50.98 / 26.98=1.890.

[0058] Next, for the calcined pellets for reduction involved in the present invention, it is also important to manage the porosity of the pellets. That is, by making the calcined pellets for reduction porous (more than 20%, preferably more than 30%), the number of contact points between the pellets can be reduced, thereby reducing the contact between the metal irons, preventing mutual fusion, and further contributing to the prevention of the aforementioned clusters. In this regard, when the porosity is less than 20%, it is not effective for preventing fusion. It should be noted that from the perspective of strength, the upper limit is about 60%.

[0059] Next, the method for producing the fired pellets according to the present invention is described. In the production of the fired pellets for reduction according to the present invention, in order to achieve the above-mentioned relationship between the slag component (Al2O3+MgO+SiO2) and the total iron (T.Fe) of the obtained fired pellets with high viscosity, for example, the following combination can be considered, wherein one or more iron ores originally having the above-mentioned relationship are selected and used to combine and use two or more iron ores showing the above-mentioned relationship. For example, combining the iron ore produced in Australia such as Figure 1 One or more of the iron ores (brands) shown above are prepared, and a binder such as bentonite and quicklime, and auxiliary materials are added as needed, and granulation is performed.

[0060] When the calcined pellets are loaded into a solid reduction furnace for reduction, it is important that the pellets do not form the aforementioned clusters in the high-temperature reducing atmosphere in the furnace. For this reason, in the present invention, LOI (Loss on Ignition) is particularly focused and its suitability value is studied. That is, in the production method according to the present invention, the LOI (Loss on Ignition) value is made 5% or more, and the following is made: Figure 1 Some of the iron ores (A to Z) shown are selected and used (blended) to satisfy LOI ≥ 5%. This can more effectively reduce clusters. This is because when volatile components such as crystal water dissociate and gasify during the firing process of the pellets and dissipate outside the pellets, the volume of the mineral phase remaining in the pellets shrinks, and gaps are generated between the mineral phases.

[0061] Next, in the manufacturing method of the present invention, in order to achieve the above-mentioned LOI ≥ 5% as the iron-containing raw material, it is preferred to perform pretreatment such as de-crystallization water treatment on the iron ore used so that LOI ≤ 2%. This is because most iron-containing raw materials such as raw iron ore contain a large amount of crystal water, so the pellets are often broken due to the water vapor generated by the crystal water during granulation. Therefore, the temperature has to be raised slowly. In addition, productivity is hindered.

[0062] In the above-mentioned pretreatment such as removal of crystal water, the above-mentioned evaluation of LOI is preferably managed using a measured value at the outlet side (discharge position) of a granulator such as a rotary kiln.

[0063] [Example]

[0064] <Example 1>

[0065] This embodiment (including comparative examples) clarifies how the relationship between T.Fe of the calcined pellets for reduction and the highly viscous slag components (Al2O3+MgO+SiO2) affects the clusters in the solid reduction furnace.

[0066] The iron-containing raw materials used in the implementation, namely iron ore, are mainly Figure 1 One or more of the Australian iron ores (A to Z) shown above, and auxiliary materials and reagents (such as commercially available Al2O3 reagents) are blended as needed. Table 1 shows examples of the blending.

[0067] One or more of the above Australian raw materials (for example, Figure 1 All the raw materials of (A to Z) were crushed, and then granulated into 9 to 16 mm in size by a pelletizer while adding water. The obtained pellets after granulation were placed in a dryer for drying at 110°C for 24 hours, and then placed in an electric furnace, heated at 7°C / min, kept at 1250°C for 10 hours, and then cooled at a rate of 7°C / min. The porosity and cluster index were used to evaluate the sintered pellets shown in Table 1.

[0068] (Cluster evaluation test)

[0069] 500g of sample was placed in a 100mmφ vertical cylindrical furnace and heated to 1000℃ in a N2 atmosphere. After reaching 1000℃, reducing gas was introduced at 24NL / min. The composition of the reducing gas was H2:N2=20:80 by volume. 2The sample is loaded and kept for 3 hours, and then cooled in a N2 atmosphere to produce reduced iron. Then, the obtained reduced iron is sieved with 16 mm, which is the maximum size of the sintered pellet monomer, and the weight Wa (g) of the sieve is measured. Then, the sieve is placed in a cylindrical container (132 mmφ×700 mmL) of a type I testing machine, rotated at a rotation speed of 30 rpm for 5 minutes, and then sieved with 16 mm to measure the weight Wb (g) of the sieve. Then, it is evaluated as a cluster index proportional to the ratio of unbroken clusters Wb / Wa.

[0070] (Porosity)

[0071] The porosity of the fired pellets was evaluated by measuring the true density after measuring the apparent density. As shown in Table 1, it was confirmed that the cluster index of Examples 1 to 5, in which (Al2O3+MgO+SiO2) / T.Fe was 0.09 or more, was less than 7, and the fired pellets had good properties.

[0072] [Table 1]

[0073]

[0074] It should be noted that the following Table 2 shows the component compositions of the fired pellets obtained in Examples 1 and 2 in Table 1. [Table 2]

[0075] (quality%)

[0076] T.Fe FeO <![CDATA[SiO2]]> CaO <![CDATA[Al2O3]]> MgO C / S Example 1 64.9 0.2 3.1 1.2 2.7 0.2 0.4 Example 2 62.5 0.4 4.9 2.9 2.3 0.3 0.6

[0077] <Example 2>

[0078] Next, a test was conducted to evaluate whether the granules could be fired without being damaged during granulation by subjecting the samples of Example 5 shown in Table 1 to a pretreatment for removing crystal water. The heating rate was 200° C. / min.

[0079] The results show that depending on whether the water of crystallization is removed by de-crystallization treatment, for example, if a large number of pores remain in the de-crystallized ore, it will cause cracking. On the other hand, if the de-crystallization treatment is sufficiently carried out, there will be no cracking. Moreover, if the LOI of the ore before treatment is sufficiently high, even if the LOI of the ore after de-crystallization treatment becomes low, it is possible to prepare pellets of good quality.

[0080] [Table 3]

[0081]

[0082] <Example 3>

[0083] The reduced iron (sample at the time of measuring Wa) obtained by the same method as in Comparative Example 2 of Example 1 (cluster evaluation test) was pulverized to obtain particles with a particle size of 3 mm or less.

[0084] These were mixed with the raw materials before firing of Comparative Example 2, and fired pellets were produced using the method of Example 1. The crushing strength of the produced fired pellets was measured. The results are shown in Table 4.

[0085] "M.Fe" in Table 4 is derived from metallic iron (M.Fe) contained in reduced iron. Examples 10 to 12 used reduced iron with M.Fe = 78 mass%. Example 13 used reduced iron with M.Fe = 80 mass%. As a result, it can be seen that the strength of the pellets is improved by mixing M.Fe into the raw materials. Since clustering is promoted by the increase in powder, clustering can be suppressed by increasing the strength of the fired pellets. In addition, it is believed that the reason why the strength of the fired pellets is improved by adding M.Fe to the raw materials is that the reduced iron powder is oxidized and generates heat during the firing of the fired pellets, so the bonding between adjacent particles is promoted.

[0086] [Table 4]

[0087]

[0088] In this specification, L as a volume unit means 10 -3 m 3 The symbol "N" attached to the volume unit of gas indicates the volume of gas at 0°C and 101325 Pa as the standard state. The unit of rotation speed rpm indicates the number of rotations per minute.

[0089] Industrial Applicability

[0090] The solid reduction calcined pellets according to the present invention are mainly developed for application in hydrogen-based direct reduction processes, and can of course also be used as a raw material used in blast furnaces and the like.

Claims

1. The calcined pellets for reduction are characterized by: The ratio of the high viscosity slag components (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (1): remember (Al2O3+MgO+SiO2) / T.Fe≥0.09· · · (1) Wherein, Al2O3: Al2O3 component concentration in the fired pellets (mass %) MgO: MgO content in the fired pellets (mass %) SiO2: Concentration of SiO2 in the fired pellets (mass %) T.Fe: The T.Fe component concentration (mass %) in the fired pellets.

2. The calcined pellets for reduction are characterized by: The ratio of the high viscosity slag components (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (2): remember (Al2O3+MgO+SiO2) / T.Fe≥0.12· · · (2) Wherein, Al2O3: Al2O3 component concentration in the fired pellets (mass %) MgO: MgO content in the fired pellets (mass %) SiO2: Concentration of SiO2 in the fired pellets (mass %) T.Fe: The T.Fe component concentration (mass %) in the fired pellets.

3. The calcined pellets for reduction according to claim 1 or 2, characterized in that: The porosity is more than 20%.

4. The calcined pellets for reduction according to any one of claims 1 to 3, characterized in that The porosity is more than 30%.

5. A method for producing calcined pellets for reduction, characterized in that: In the production of the calcined pellets for reduction according to any one of claims 1 to 4, the raw materials blended so as to have an average LOI (loss on ignition) of 5% or more are used as the iron-containing raw materials for reduction and calcination.

6. The method for producing calcined pellets for reduction according to claim 5, wherein: The iron-containing raw material used was a raw material that had been pre-treated in advance to remove water of crystallization so that the average LOI (loss on ignition) was 2% or less.

7. The method for producing calcined pellets for reduction according to claim 5 or 6, wherein: The pretreatment for removing crystal water uses a rotary kiln for heating and drying, and the average LOI (loss on ignition) of the iron-containing raw material is a value measured by sampling at the kiln outlet.

8. A method for producing calcined pellets for reduction, characterized in that: A raw material containing M.Fe is blended to prepare a mixed raw material containing 4 mass % or more and 24 mass % or less of M.Fe, and the mixed raw material is granulated and fired.

9. The method for producing calcined pellets for reduction according to claim 8, wherein: The raw material is reduced iron with a particle size of less than 3 mm that is reduced in a solid reduction furnace.

10. The method for producing calcined pellets for reduction according to claim 9, wherein: The reduced iron contains 78 mass % or more of M.Fe.

Citation Information

Patent Citations

  • Controlling device of wall thickness in mandrel mill

    JP1984010411A

  • Calcined lump ore and its production

    JP1987037325A

  • Raw material for iron manufacture

    JP1988262426A

  • Reduction raw material, and method for producing reduction raw material

    JP2017119910A